2016
DOI: 10.1016/j.compositesb.2016.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of novel auxetic structures based on re-entrant hexagon design produced from braided composites

Abstract: This paper reports the first attempt of developing macro-scale auxetic structures based on re-entrant hexagon design from braided composite materials for civil engineering applications. Braided composite rods (BCRs) were produced and arranged as longitudinal and horizontal elements to produce three types of auxetic structures: (1) basic re-entrant hexagon structure, (2) basic structure modified by adding straight longitudinal elements and (3): structure-2 modified by changing structural angle. The influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Re-entrant foams are the most common auxetic cellular-network materials, examples include 2D re-entrant honeycombs [18,40], 3D re-entrant foams [4], double-arrowhead re-entrant structure [41], star-shaped structure [42]. In this paper, we study the elastic properties of interpenetrating composites which are reinforced by three different types of regular re-entrant fibre-networks.…”
Section: Geometric Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Re-entrant foams are the most common auxetic cellular-network materials, examples include 2D re-entrant honeycombs [18,40], 3D re-entrant foams [4], double-arrowhead re-entrant structure [41], star-shaped structure [42]. In this paper, we study the elastic properties of interpenetrating composites which are reinforced by three different types of regular re-entrant fibre-networks.…”
Section: Geometric Structuresmentioning
confidence: 99%
“…It has already been experimentally demonstrated that composite plates reinforced by an auxetic fibre-network exhibits a negative Poisson's ratio in the thickness direction [39]. Composites reinforced by a re-entrant hexagonal honeycomb are also found to exhibit strong in-plane auxetic behaviour [40]. Available publications on composites with auxetic behaviour are very limited and the properties are in general anisotropic.…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid braiding angles introduce geometrical incompatibility into the longitudinal deformation of the structure, which leads to improved longitudinal stiffness without compromising the bending. The constant and varied braid angles on the conical mandrel’s surface determine the strength of the twist, and the mechanical properties can be designed using an auxiliary structure [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such materials have their potentials as technical textiles in the medicine, automobile, marine and aerospace, architecture, civil engineering, and footwear industries, etc., for filtration where the pore opening size can be controlled by tension, vibration damping, shock absorbency, smart bandages, dental floss with in-built drug release, compression hosiery, seat cushion material, fastening devices, reinforcements in advanced composites, padding material for better forefoot pressure relief in high-heeled shoes, as well as apparel textiles (maternity dresses, bra cups, leggings, children’s wear during the period of growth, support garments, etc.) [4,5,6,7,8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%